A multicentre prospective analysis of the incidence of pemphigoid diseases in Turkey. (12th October 2021) - Durdu, Murat; Bozca, Burçin Cansu; Enli, Servinaz; Yazıcı Özgen, Züleyha; Yaylı, Savaş; Aktan, Şebnem; Mutlu, Derya; Erturan, Ijlal; Ayvaz Çelik, Havva Hilal; Melikoğlu, Mehmet; Pala, Erdal; Gürsel Ürün, Yıldız; et al.
Abstract: Background: The differentiation between the pemphigoid diseases is essential for treatment and prognosis. In Turkey, data on the incidence of these diseases are insufficient. Our aim in this study is to determine the incidence, demographics and clinical characteristics associated with diseases of the pemphigoid group. Methods: We prospectively analysed 295 patients with pemphigoid who visited dermatology clinics of tertiary referral hospitals in 12 different regions of Turkey within a year. The diagnosis was based on clinical, histopathological, direct immunofluorescence (DIF) and serological (multivariant enzyme‐linked immunosorbent assay [ELISA], indirect immunofluorescence and mosaic‐based BIOCHIP) examinations. Clinical and demographic findings, aetiological factors and concomitant diseases observed in the patients were recorded. Results: A total of 295 (female/male ratio: 1.7/1) patients with pemphigoid were diagnosed in 1‐year period. The overall incidence rate of pemphigoid diseases was found to be 3.55 cases per million‐years. The ratio of pemphigoid group diseases to pemphigus group diseases was 1.6. The most common pemphigoid type was bullous pemphigoid (BP, 93.2%). The others were epidermolysis bullosa acquisita (3.1%), pemphigoid gestationis (2.4%), linear IgA disease (1%) and mucous membrane pemphigoid (0.3%). The most common (26.8%) possible trigger of the bullous pemphigoid was gliptin derivative drugs. The most common concomitant diseases with pemphigoid were cardiovascular (27.8%) and neurological diseases (23.7%). Conclusions: This study showed that the increased frequency of bullous pemphigoid reversed the pemphigoid/pemphigus ratio in Turkey. Further studies are warranted regarding the reasons for this increase.